IMPACT OF EDUCATIONAL INTERVENTION ON PRESCRIBING PATTERNS OF NON-STEROIDAL ANTI-INFLAMMATORY DRUGS IN MEDICINE AND ORTHOPEDICS DEPARTMENT OF TERTIARY CARE HOSPITAL – AN AMBISPECTIVE STUDY - Dr. Dwit Vora; Dr. Anusha Vohra; Dr. Parthil Patel; Dr. Ruchi Mathur; Dr. Pawan Sharma; Dr. Mohammed Muzahid (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely prescribed in both Medicine and Orthopedics department, often accompanied by concerns over adverse effects such as gastrointestinal complications. This study evaluates prescription practices for NSAIDs in both specialties, focusing on polypharmacy, generic prescribing, and adherence to safety measures, intending to improve patient care and rational drug use. Method: A pre- and post-intervention analysis was conducted at a tertiary care center, analyzing 913 prescriptions from both departments. Parameters assessed included the average number of drugs per prescription, the percentage of generic NSAIDs prescribed, co-prescription rates of gastroprotective agents, inappropriate combinations per Beers Criteria, and the use of COX-2 selective NSAIDs. Interventions involved a teaching session for clinicians focusing on rational NSAID use, with data analyzed via paired t-tests and chi-square tests to determine statistical significance. Result: Post-intervention, there was a significant reduction in the average number of drugs per prescription in Medicine (4.2 to 4.0, t=2.45, p=0.015), though this effect was not significant in Orthopedics (5.1 to 5.0, t=1.35, p=0.188). The percentage of generic NSAIDs showed a non-significant increase in both Medicine (40% to 41%, t=1.20, p=0.24) and Orthopedics (30% to 35%, t=1.42, p=0.17). Co-prescription of gastroprotective agents significantly increased in Medicine (50% to 60%, chi-square=3.84, p=0.05), but changes in Orthopedics were non-significant. No significant improvements were observed in the reduction of inappropriate combinations or the use of COX-2 selective NSAIDs. Conclusion: The educational intervention was associated with positive, though modest, improvements in NSAID prescribing practices. Increased use of generic drugs, adherence to essential medicine lists, reduced use of injections, and improved gastroprotective co-prescriptions emphasize the intervention's effectiveness in promoting safer NSAID use.